PENERAPAN PEMBELAJARAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INGGRIS MATERI MY SCHOOL ACTIVITIES KELAS VII.1 DI SMP NEGERI 8 PEKANBARU - Irmayani, Irmayani (Komunitas Manajemen Kompetitif, 2023)
ABSTRACK This study aims to determine to improve students in English subjects, My School Activities in the form of Discovery Learning Model in class VII.1 at SMP Negeri 8 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are the students of class VII.1 in SMP Negeri 8 Pekanbaru with a total of 37 students consisting of 18 male students and 19 female students. The data obtained in the form of English learning result obtained from the test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 45% with inactive classification. While in cycle II result of student in learning experience increase to become 55% with very active classification. This situation shows that improvements in English process with Discovery Learning model in English subjects, My School Activities in grade VII.1 students at SMP Negeri 8 Pekanbaru can be said to be fully successful.